Can good impression and feedback-seeking behavior help Chinese graduates get a job?. Issue 1 (11th May 2015) - Ren, Run; Sun, Judy Y; Zhang, Yichi; Chen, Yunyun; Liu, Chunching
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the effect of feedback seeking (FBS) and impression management (IM) on candidates' evaluative performance and final hiring decision in a recruiting assessment center (AC) by a multinational corporation (MNC) in China. Design/methodology/approach – The authors adopted a mixed-methods design. The authors first surveyed 234 candidates and 12 recruiting managers as assessors in four Chinese cities in one year. The authors then collected 23 candidates' qualitative data in the forms of online blogs, diaries or letters sharing their recruitment experiences from 2005 to 2014. Findings – The quantitative results showed that both candidates' FBS and IM behaviors were positively related to their evaluative performance, yet with no significant effects on hiring decision. However, the interaction of FBS and IM significantly reduced the likelihood of a positive evaluative performance and hiring decision. Qualitative findings showed that IM was adopted by the candidates, and encouraged by the firm in the initial period of AC. Implicit FBS behavior was also found in the qualitative data. Practical implications – The results offer important practical implications. For applicants, success in job search depends on one's overall ability and capacity, while proper FBS and initial IM may be helpful to get in the race. At the firm level, MNCs need to adopt innovative strategies to win the "war for talent" in campus recruiting to cope with the deficiency in the educational focus. Originality/value – The authors adopted a mixed-methods approach to examining the dynamics of AC process in campus recruiting processes. This study is among the first examining the interactions of FBS and IM in the selection research.